2020
DOI: 10.1515/med-2020-0128
|View full text |Cite
|
Sign up to set email alerts
|

GABRD promotes progression and predicts poor prognosis in colorectal cancer

Abstract: Little is known about the functional roles of gamma-aminobutyric acid type A receptor subunit delta (GABRD) in colorectal cancer (CRC). The expression of GABRD between CRCs and adjacent normal tissues (NTs), metastasis and primary tumors was compared using public transcriptomic datasets. A tissue microarray and immunohistochemical staining (IHC) were used to determine the clinical and prognostic significance of the GABRD in CRC. We used gain-of-function and loss-of-function experiments to investigate the in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…In addition, GABRD gene may be a prognostic marker in gliomas with low expression, and it is associated with poor prognosis [ 10 , 11 ]. In another study, GABRD expression was found to be significantly lower in IDH wild-type diffuse gliomas compared to IDH mutant tumors [ 12 ], and patients with high GABRD expression had a better prognosis than those with low GABRD expression [ 13 ]. Taken together, it is suggested that the functional mechanism of GABRD in cancer needs to be investigated on specific cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GABRD gene may be a prognostic marker in gliomas with low expression, and it is associated with poor prognosis [ 10 , 11 ]. In another study, GABRD expression was found to be significantly lower in IDH wild-type diffuse gliomas compared to IDH mutant tumors [ 12 ], and patients with high GABRD expression had a better prognosis than those with low GABRD expression [ 13 ]. Taken together, it is suggested that the functional mechanism of GABRD in cancer needs to be investigated on specific cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…1C). All of these genes have been shown to play important roles in tumor progression [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Interestingly, 8 of these 17 genes have been identified as hypoxia-associated genes, including CA9, gamma-glutamyltransferase 6 (GGT6), KISS1 receptor (KISS1R), enolase 2 (ENO2), hypoxia-inducible lipid droplet-associated protein (HILPDA), EGL-9 family hypoxia inducible factor 3 (EGLN3), endothelial cell specific molecule 1 (ESM1), and NDUFA4 mitochondrial complex-associated like 2 (NDUFA4L2) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…KCNMA1 has been used as a prognosis-related biomarker in several tumors and is strongly correlated with tumor metastasis and calcium channels ( Khaitan et al, 2009 ; Zhang and Yan 2014 ; Wang et al, 2018 ). GABRD is widely reported to be closely associated with colon cancer ( Niu et al, 2020 ; Wu et al, 2020 ). KCNJ15 has been closely related to potassium channels and identified as a molecular marker by investigators in ccRCC ( Liu et al, 2019 ; Zhang J. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%